Disability and the Elderly in their Freedom of Interaction with the Spanish Administration - Sánchez Ballesteros, Vanesa (The Age of Human Rights Journal, 2023)
Disability and elderly people are considered special groups due to their high degree of vulnerability, and their welfare must be supported by public measures that reinforce the guarantees of their rights and freedoms. Although new technologies open up a world of possibilities in all areas of life, their use can hinder, in some cases, the development of the rights of these groups because their practice is a complex novelty, especially in the area of communication between citizens and the Public Administration. Therefore, this study focuses on the analysis of the impact of ICTs on the right to freedom of access of persons with disabilities and the elderly.